Flying high... safely - training theory applications to reduce high jump injuries - Myers, B. (Techniques Magazine, 2023)
Most common high jump injuries have been well documented and include the take-off knee, back, lower leg and foot injuries. Learning from the take-off forces (rotational and linear) that impact the high jumper (up to 5.6 x the jumpers body weight-Milan Coh-2010 research), it is prudent to design a training program to withstand these extreme forces. In following the Stress-Adaptation Theory, first documented by Dr. Hans Selye (1950), it is important to systematically reinforce these potential injury areas of a high jumper´s body that repeatedly need to resist these forces without succumbing to injuries, either chronic or acute.